A Qualitative Study on Consumption Motivations in Turkish Marriage Rituals - Elif Boyraz; Çiğdem Aliçavuşoğlu (Hitit Ekonomi ve Politika Dergisi)
The main aim of this study is to reveal how cultural change and interaction shape today's marriage rituals and to what extent this situation is reflected in marriage consumption. This study is a non-experimental cross-sectional field study that analyzes data on variables collected over a period of time in a target sample. As a result of the study conducted, no scale that reveals marriage rituals and their reflection on consumption was found. For this reason, in order to explain the mechanisms behind the concepts and findings in the literature in depth, the method of this study was determined as qualitative method. The sample of the study was determined according to the maximum variation sampling method. The sample, which was determined according to this method, consists of those who will get married in the next year (2022), those who have been married until five years ago and mothers-in-law. As a result of the thematic analysis, the categories were determined as; meeting, marriage proposal, asking for the girl’s hand in marriage - betroth- engagement, bundle, henna night, to fetch the bride, marriage and wedding, photo shooting, shopping, jewelry sharing, material effect, the effect of the pandemic and using social media in ritual consumption. Themes were identified by analyzing the categories. Marriage rituals, consumption of marriage rituals, jewelry, the pandemic and social media are the themes identified. Findings were discussed in the line of relevant literature.